Analysis of chemical engineering curriculum to improve process safety competency - Sofri, Salwa; Reddy Prasad, D. M.; Bin Azri, Mohammad Hazwan; Timbang, Aisah (International journal of occupational safety and ergonomics, 2023)
Continuous process safety (PS) development is the key to maintaining a good PS system, and its competency plays a substantial role. However, PS incompetency can still be demonstrated in several process-related accidents, particularly major catastrophic incidents. To mitigate this gap, universities' PS education is analysed. Because PS is an important element of chemical engineering (CE), this study seeks to identify the most prevalent PS subjects taught in the top 300 Quacquarelli Symonds ranking (2019) universities. Findings indicate that PS education remains insufficiently addressed in undergraduate CE curricula over the years. Twelve common topics, i.e., human factors; management of hazards, incidents, and risk; design; fire and explosion; legislation and standards; sustainability; process control; economics; toxicology; and software are identified. Notably, sustainability is acknowledged to be a new common PS topic, depicting its demand for industrial evolution. Ultimately, strengthening the collaboration between universities and industries is required to develop graduates' PS competency. Abbreviations: ALARP: as low as reasonably practicable; CAD: computer-aided design; CE: chemical engineering; ETA: event tree analysis; FTA: fault tree analysis; FMEA: failure mode and effect analysis; HAZAN: hazard analysis; HAZID: hazard identification; HAZOP: hazard and operability; HSE: health, safety and environment; HYSYS: Hyprotech Systems; LCA: life cycle analysis; LOPA: layer of protection analysis; MS: Microsoft; ORP: occupational risk prevention; PC: personal computer; PHA: process hazard analysis; PS: process safety; PSM: process safety management; QS: Quacquarelli Symonds; SMS: safety management system.